The role of financial advisors’ reputation in M&A deals in emerging markets - Galhardas, Carolina da Silva (2023)
In recent years, cross-border Mergers and Acquisitions (M&A) have become increasingly popular, and the success of these complex transactions is heavily reliant on the involvement of financial advisors. This study investigates the impact of financial advisor reputation on the performance of acquirers from developed countries in M&A deals with targets from emerging markets. The reputation of financial advisors is evaluated by classifying them into two groups based on the total value of deals advised: top-tier and non-top-tier advisors. A comprehensive analysis of 896 M&A deals reveals a positive association between financial advisor reputation and acquirer performance in M&A deals with public targets. However, this relationship was not found in transactions involving private or subsidiary targets. The results suggest that engagement with a top-tier financial advisor leads to a 0.726% increase in the acquirer's CAR when dealing with public targets, compared to acquirers who choose non-top-tier advisors. It was also found that top-tier financial advisors charge an average of 0.0923 percentage points more in advisory fees than their non-top-tier counterparts. Moreover, the study shows that top tier advisors do not necessarily lead to a significant positive impact on the acquirers’ CAR in advising on the largest deals and that their resolution time is comparable to that of non-top-tier advisors.